Upaya Literasi Digital dalam Membangun SDM Unggul pada SMPN 7 Amarasi Barat di Desa Tooboun, Amarasi Barat, Kupang, NTT - Saragih, Herlina JR; Suhirwan, Suhirwan; Mahardika, Riza (representamen, 2020)
There are many regions in Indonesia that should be paid more attention by the government. Without us knowing and realizing, apparently there are still many people who really need it, whether it's clothing, food and shelter, and proper education. This study uses descriptive qualitative data in the eastern part of Indonesia, namely the village of Tooboun, Amarasi Barat, NTT. The houses are also not as good as in the area of Java. The existence of NTT communities like this, will cause a dehumanization of its own, due to lack of access to all needs, and ultimately lead to a decrease in Human Resources (HR) from the community itself. The existence of demographics like this, makes them feel discriminated from certain groups. So, in this study, the writer wants to do how to develop the human resources of the village community of Tooboun, Amarasi Barat, NTT by using Media Literacy as the feasibility of life as social beings, each of whom has independence in life. This research was created to provide a basis, evaluate media literacy efforts and contextualize them relative to the current scope of media. Keywords: NTT Society, Media Literacy, Socio-Cultural Values